„Monologami są rozmowy” . Liryczność w Pierścieniu Wielkiej Damy Cypriana Norwida - Trzcionka, Joanna (Colloquia Litteraria, 2016)
“Dialogues are Monologues”. Lyricism in Cyprian Norwid’s The Ring of a Great Lady The article attempts to show how lyricism as an essential component of Cyprian Norwid’s The Ring of a Great Lady affects the artistic shape of the work. This issue is shown by the observation of selected structural elements of the drama, such as time, space and the construction of the main character. In the work the space of the drama and time of the action have been used as metaphors and moved into the sphere of the protagonists’ spiritual experiences. Both time and space planes undergo subjectivism which is the result of lyricism that pervades Norwid’s work. A window – the element of the theatre building plays a prominent role in shaping time and space of the drama. It is a point that links the outside world to a close space of the play which becomes simultaneously extended. The point performs the function of the prism through which this world penetrates the author’s life. In poetical expressions the window also becomes a place of the protagonists’ overcoming time-space limitations. The protagonists’ lyrical monologues, above all Mak-Yks’s monologues, show the evolution of the man’s personality. This character is externally passive, inactive though he exudes the unparalleled inner energy. The lyricism contained in dialogues and monologues, the shaping of a poetic language, its continual tension between expressing his personal experiences and a parallel general reflection initiate a multidimensional, symbolic significance of the drama. The analysis of lyrical fragments also shows that Mak-Yks, likewise Norwid’s other protagonists share a distinctive feature with the author, and the conclusions lead us to reflect that The Ring of a Great Lady is a lyrical drama.